KETAATAN ABDI DALEM KATOLIK DALAM KERATON NGAYOGYAKARTA (Refleksi Teologis: Memaknai Ketaatan Kristus Sebagai Sang Pembawa Berkat) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
Abdi dalem is the way of life for some Javanese people in Yogyakarta. They did to get inner peace and happiness in their life more than to seek wealth or social status. They lives in three tradisional wisdom: ngabekti, submission, and obedience as part of the tradition of worshiping in  Ngayogyakarta Palace.The three pearls of wisdom are manifestations of the concept of “practice” (laku) as a form of obedience in Javanese philosophy. First, they believe that human  beings live in two cosmos: the macro-cosmos (jagad-ageng) and the micro-cosmos (jagad-alit). Hence, the universe control all about life, and human beings depend on them that can determine their’s salvation.So they try to manage and maintain a close relationship in unity with the universe so that humans receive prosperity and salvation. Second, the world has limited by the presence of the dying, but they believe there is life after death. So that the “practice” leads man to be united with the Creator. Third, the “practice” is understood as an effort to looking for inner peace and become a “blessing” for herself and her family.For this reason, the question to be answered in this research is: how Abdi Dalem reflects on the practice of obedience in order to be a turning point to understanding the obedience of Jesus Christ to God.Obedience was based on human freedom, like Christ who emptied himself to obey his Father. So the practice of obedience contains the elements of kenosis in the practice of self-emptiness, self-control, and humility. The practice of obedience is also based on human freedom which is directed towards prosperity and salvation. The obedience will bring “blessings” to him, his family, and the society in which he was. Finally, perfect obedience requires a foundation: faith in Christ who has revealed himself, suffered, died, and then rose to bring redemption to mankind.
Keywords: ketaatan; kenosis; pembebasan; iman; Kristus; laku; sembah bakti; slamet